(untitled) (Technological Innovations Journal, 2024)
Financial education is a fundamental component in the formation of high school students, as it is linked to their ability to make financial decisions that could influence their long-term economic well-being. This study aims to analyze the relationship between financial education and financial decision-making among students in emblematic schools in the city of Puno, Peru, during the 2024 period. The research employs a quantitative approach with a non-experimental, cross-sectional, and correlational design. A representative sample of 572 fifth-year high school students from three emblematic schools in the city was surveyed. The results indicate a moderate positive relationship between financial education and decision-making, with a Spearman correlation coefficient (rho = 0.451). This suggests that, while financial education is an important factor, it is not the only determinant in financial decision-making. These findings highlight the importance of continuing to promote financial education to improve students’ economic well-being; however, they also suggest that other factors may influence decision-making. Future research is encouraged to consider contextual and social variables to gain a deeper understanding of the factors affecting financial decision-making in high school students.